Experimental and theoretical performance of finned-single effect solar still. Issue 37 (8th August 2016) - El-Naggar, M.; El-Sebaii, A.A.; Ramadan, M.R.I.; Aboul-Enein, S.
Abstract: A conventional single basin solar still and modified unit with finned-basin liner were constructed and investigated experimentally and theoretically. The stills were tested outdoors on typical days of June 2014 under Tanta prevailing weather conditions (Lat. 30° 47′ N, Egypt). The energy balance equations of the considered stills were formulated and solved analytically. Suitable computer programs were prepared for optimizing and predicating the thermal performance of the considered systems. Comparisons between experimental and theoretical results were performed. Comparisons of the obtained results with those presented in previous studies were also made. The daily productivities of the conventional and modified stills were found to be 4.235 and 4.802 (kg/m 2 d) with daily efficiencies of 42.36 and 55.37%, respectively. The convective heat transfer coefficient from the finned plate was increased by 3.6 times compared to the case without fins. The agreement between measured and calculated daily productivity is fairly good. The cost of 1 L of distillate water was found to be 0.28 LE.